A study on the borrowing patterns of the middle school students (Grades 4-7) of the Asterio J. Katigbak Educational Media Center (KEMC) of the Ateneo de Manila Grade School through analysis of book circulation - Albania, Pamela S.; Apolinario, Rhea Rowena U.; Lapuz, Elvira B. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2010)
The study was conducted in order to analyze the borrowing patterns of the middle school students (Grades 4-7) of the Asterio J. Katigbak Educational Media Center (KEMC) through analysis of book circulation. It was hypothesized that there is no significant relationship between book borrowing and the and the following: (1) student's grade level; (2) students' parent's profession or field, and; (3) age of materials. The study also determined the percentage of collection circulation by grade levels, the average circulation per volume, and the reading interests of middle school students.
The data were gathered using the Library Integrated System Administration(LISA) 6.0 about the collection composition and age and to measure use of materials in the KEMC. Actual circulation statistics were examined to reveal Grade Seven students' borrowing history for the last three years. The data were used to determine book circulation relationship to the following; student's grade level, parent's profession or field, and age of materials. A survey was also conducted to gather information on student's reading interest, the sources where they get books from, the people who guide them to read, and the reasons that hinder them to read more.
The results showed that there is significant relationship between book borrowing and student's grade level and age of materials, therefore, rejected the hypothesis. However, ,parent's profession or field of the students was found to have no effect with book borrowing and thus, the hypothesis cannot be rejected. Fiction books proved to be highly circulated subject area among the collections and has the highest percentage of collection circulated throughout the middle school. Likewise, students were highly interested in borrowing newly copyrighted books. The nonfiction books about Fine Arts and History are the highly interesting, while Language and Literature were the least interesting topics. The study showed that students were mostly self-purchasing books and students have high self-reliance on reading guidance. Too much school work was the main obstruction to student's leisure reading.
Based on the findings, it is recommended that the library should improve a three year acquisition development plan on the basis of circulation turnover and copyright date. The librarian should develop a collection of non-print materials to provide a variety of online reference sources that are reliable, credible, and up-to-date in different subject areas. Although the study revealed that teachers and librarians were least to rely on reading guidance, it is still important to provide library instruction and modelling on book selection strategies to properly guide the students in book selection.
Vita.
Special Problem (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: Asterio J. Katigbak Educational Media Center (KEMC) Ateneo de Manila Grade School; School children -- Philippines -- Quezon City; School libraries -- Circulation and loans. -- Philippines -- Quezon City